Answer:
X = 7
Explanation:
Simplifying
7x + -9 + 4x + 22 = 90
Reorder the terms:
-9 + 22 + 7x + 4x = 90
Combine like terms: -9 + 22 = 13
13 + 7x + 4x = 90
Combine like terms: 7x + 4x = 11x
13 + 11x = 90
Solving
13 + 11x = 90
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-13' to each side of the equation.
13 + -13 + 11x = 90 + -13
Combine like terms: 13 + -13 = 0
0 + 11x = 90 + -13
11x = 90 + -13
Combine like terms: 90 + -13 = 77
11x = 77
Divide each side by '11'.
x = 7
Simplifying
x = 7